Miraculous character in Fadhil Al-Azzawi's Novels - Jinan Mohammed Farhan; Atheer Mohammed Shihab (College of Education for Women, 2019)
this research adopts the study of experimentational fiction in the characters for the writer Fadhil Al-Azzawi ,which appear in the miraculous characters that the writer creates in his enumerative paragraphs , and these characters are featured by there reveling on traditions which is prevalent in the formation of these characters, The research also included theoretical beginning foe experimental fiction and miraculous characters, followed by analysis and examination of these characters in the writer`s texts, finishing by an epilogue for the results of the research , giving the references and resources we depended on writing this research .